Ischaemic strokes and myocardial infarctions in a young male cannabis user - Annabelle Culling; Eluzai Hakim; Oliver Pearce; Michelle Dharmasiri (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2024)
A case of a 29-year-old man is described who presented with sudden onset occipital headache and right eye vision loss. Computerised axial tomographic scanning (CT) of the brain demonstrated multifocal bilateral areas of low attenuation. A brain magnetic resonance imaging (MRI), confirmed bilateral acute cerebral infarctions. In view of a significant elevation in troponin levels at a previous admission, cardiac viability magnetic resonance imaging (cvMRI) was carried out and demonstrated acute infarction affecting the left ventricular apex and multiple smaller infarcts elsewhere within the myocardium. On this occasion he did not complain of chest pain. The electrocardiogram (ECG) showed ischaemic changes. The patient denied a family history of ischaemic heart disease, diabetes mellitus, hypertension and hypercholesterolaemia, but admitted to daily use of cannabis and cigarette smoking. We considered the regular use of cannabis as a possible aetiology in the development of multi-territory cerebral and myocardial infarcts, previous myopericarditis and left ventricular dysfunction.